Les barrios de Caracas ou le paradoxe de la métropole - Virginie Baby-Collin (Cahiers des Amériques Latines)
Since the beginning of their growth in the twenties, the poor suburbs of Caracas have been undergoing two processes: exclusion or urban marginalization and integration in the city. However, the economical and social crisis which affected Venezuela in the eighties induced substantial changes: forms of withdrawal in the barrios, while violence grows and the bonds change between formal and informal city.